2011
DOI: 10.5694/mja11.10379
|View full text |Cite
|
Sign up to set email alerts
|

When informed consent goes poorly: a descriptive study of medical negligence claims and patient complaints

Abstract: The typical dispute over informed consent involves an operation, often cosmetic, and allegations that a particular complication was not properly disclosed. With Australian courts now looking to patient preferences in setting legal standards of care for risk disclosure, medicolegal disputes provide valuable insights for targeting both quality improvement efforts and risk management activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 10 publications
3
64
0
2
Order By: Relevance
“…Details of how the informed consent complaints were identified and reviewed are described elsewhere 22. In summary, the Commission received 9115 complaints over the study period, 1898 (21%) of which proceeded to conciliation.…”
Section: A Case Study From Victoriamentioning
confidence: 99%
“…Details of how the informed consent complaints were identified and reviewed are described elsewhere 22. In summary, the Commission received 9115 complaints over the study period, 1898 (21%) of which proceeded to conciliation.…”
Section: A Case Study From Victoriamentioning
confidence: 99%
“…(The HSC data related to all complaints against doctors, regardless of who insured them.) We have previously described our method for screening claims and complaints in this sample frame to determine which ones met the definition of an informed consent dispute [11]. We recap definitions of key terms in Box 1.…”
Section: Discussionmentioning
confidence: 99%
“…The disputes were drawn systematically from litigation and conciliation files resolved over a seven-year period. In a recent report [11] we described general characteristics of this sample. In this analysis, we describe a subset that involved explicit disagreements between patients and doctors about whether a particular risk ought to have been disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that informed consent has become the minimal floor for communicating risks and benefits, confusing a much-needed process for patient engagement with the completion of a document. 40,41 Many patients do not read this document or understand that alternatives or no treatment are viable options. 15,42,43 Furthermore, SDM should not be implemented as a printout or an electronic checklist to document that a decision aid was given to the patient.…”
Section: How Should We Promote Sdm?mentioning
confidence: 99%